THE EFFECT OF ONLINE LEARNING METHODES ON STUDENT’S LEARNING ABILITIES IN STATISTICS COURSE - Zuhri Zuhri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
AbstractOnline learning is a solution given to overcome the difficulty of direct teaching and learning due to social restrictions in the Covid-19 pandemic. The purpose of this study was to determine the effect of online learning on the learning abilities of students at the institute of management science SUKMA Medan in the statistics course. This type of research is quantitative. The data collection technique in this study used research instruments, then the data were analyzed to test the hypothesis that had been determined using simple linear regression analysis techniques. The results of this study indicate that there is a positive influence of online learning on the learning abilities of students at the institute of management science SUKMA Medan in statistics courses by 68%, while the other 38% are influenced by other factors, such as environmental factors, psychological conditions or factors that are not studied.